2018
DOI: 10.1128/jcm.01982-17
|View full text |Cite
|
Sign up to set email alerts
|

Triton X-100 and Increased Volume of Test Bacteria in the Carbapenem Inactivation Method Enhanced the Detection of Carbapenemase-Producing Acinetobacter baumannii Complex Isolates

Abstract: X-100 and increased volume of test bacteria in the carbapenem inactivation method enhanced the detection of carbapenemase-producing Acinetobacter baumannii complex isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The method of TCIM modified from mCIM could reach 100% sensitivity in the detection of carbapenemase-producing A. baumannii . 9 We also found that the addition of Triton X-100 (0.1% v/v) to CIM could improve the sensitivity from 6.02% to 100% in this study. Substituting sterile water for tryptic soy broth and shortening the incubation time could simplify the test process; however, the isolates used by Liu et al differed from those used in this study.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The method of TCIM modified from mCIM could reach 100% sensitivity in the detection of carbapenemase-producing A. baumannii . 9 We also found that the addition of Triton X-100 (0.1% v/v) to CIM could improve the sensitivity from 6.02% to 100% in this study. Substituting sterile water for tryptic soy broth and shortening the incubation time could simplify the test process; however, the isolates used by Liu et al differed from those used in this study.…”
Section: Discussionsupporting
confidence: 66%
“… 8 Triton-CIM (TCIM) method, a modified mCIM, was proposed by Liu et al and also used for the detection of carbapenemase-producing A. baumannii . 9 However, the application value of Triton X-100 to CIM has not been discussed to date. The incubation time and buffer solutions were different for CIM and mCIM.…”
Section: Introductionmentioning
confidence: 99%
“…For more advanced methods such as MALDI-TOF MS, widespread implementation seems unfeasible due to complex processing and interpretation difficulties [61]. In Enterobacterales, the carbapenem inactivation method (CIM) [62,63] has been considered favorable in a modified version (mCIM) [64] with respect to sensitivity (97%) and specificity (99%), and was added to the Clinical and Laboratory Standards Institute M100 document [65]. In contrast, in the corresponding EUCAST document the CIM is mentioned as a possible alternative in Enterobacterales; however, with the accompanying information on the uncertain negative predictive value and the "disadvantage" of at least 18 h of time-to-result [53].…”
Section: Introductionmentioning
confidence: 99%
“…The comparability of results is complicated by different definitions applied by various studies of what exactly is intended to be revealed by the CIM. These definitions span a spectrum from the demonstration of the activity of acquired carbapenemases (van der Zwaluw et al, 2015, Uechi et al, 2017, Jing et al, 2018, Vu et al, 2020, Howard et al, 2020, Cui et al, 2020 to the demonstration of the activity of chromosomal OXA-51-family, with (Liu et al, 2018, Uechi et al, 2019 or without associated insertion sequence (in Yamada et al, 2020). Since the objective of CIM was to reveal information relevant to infection control, choice of therapy, and epidemiology, supplementing the results of standard susceptibility testing, the authors of the present study retain the original intention [62,66] to demonstrate the presence of acquired carbapenemases and provide the accordingly transformed results of other studies in Table 1 (bold letters), where appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…mCIM includes the use of an alternative incubation medium (tryptic soy broth versus water) and extension of the incubation time to 4 h, both of which were found to improve the assay's sensitivity for certain carbapenemases. Furthermore, several CIM variants have recently been developed to improve the CIM diagnostic performance (25), time of response (26,27), and carbapenemase class characterization (27)(28)(29). However, to date, there has been no study evaluating the effectiveness of CIM in detecting other hydrolyzing enzymes, such as ESBLs, and its direct application to clinical specimens, such as BC bottles.…”
mentioning
confidence: 99%